Parvoviruses as anti-cancer agents - Cornelis, Jan; Cziepluch, Celina; Giese, Nathalia; Rommelaere, Jean (Viral Therapy of Human Cancers, 2004)
As a result of their oncotropism, oncolytic activity, and low capacity for danger signaling, some autonomous parvoviruses open new prospects to cancer therapy. Pilot Phase I clinical trials in humans using natural parvoviruses and pre-clinical studies in animals using both wild-type parvoviruses and vector derivatives transducing various cytokines, lend credit to the possible application of these agents to the fight against cancer. The oncosuppressive effects of natural and recombinant parvoviruses are reviewed, and possible mechanisms are discussed in the light of recent findings in the field of immunotherapy, which bear relevance to the development of more potent parvovirus-based anticancer agents.